The Role of Professional Development in Enhancing Teachers’ Pedagogical Practice: An Evaluation of the Sherman Center Teacher Summer Institute - Godwin, Karrie E.; Kumaravelan, Praveen; Hossain, Shahin; Baker, Linda; Mata-McMahon, Jennifer (Sherman Center, 2025)
Professional development (PD) is seen as an avenue to improve student achievement outcomes by modifying teacher knowledge and practices. The present work focuses on evaluating one model of PD, the Teacher Summer Institute (TSI), a Sherman Center for Early Learning in Urban Communities initiative designed for urban early childhood educators in Maryland. The TSI equips teachers with tools, resources, and opportunities to acquire the necessary knowledge and skills to enhance their pedagogical practices. The TSI involves keynotes, PD sessions, collaborative working sessions, research scholars' presentations, and reflection opportunities. Through two studies, we evaluated the TSI’s impact on early childhood educators’ pedagogical practices by analyzing five years of program archival data (Study 1) and conducting a retrospective study (Study 2) in which we fielded an online survey of participating teachers. Implications for future program iterations and subsequent research evaluation efforts are discussed.
Keywords: UMBC Child Development Lab